AVALIAÇÃO DA TITULAÇÃO DE ANTICORPOS FRENTE A DIFERENTES PROTOCOLOS DE PRIMOVACINAÇÃO ANTIRRABICA EM UMA POPULAÇAO DE CÃES DE CAMPO GRANDE, MATO GROSSO DO SUL - Jeannette Leon Thames (2023)
Protection of humans against urban rabies is mainly achieved by prophylactic measures applied to dogs and cats, which include vaccines that induce minimal antibody titers (≥0.5 IU/ml). mass, many animals do not achieve protective antibody titers after vaccination. Few studies have examined factors associated with the failure of dogs to achieve an adequate antibody titer after vaccination. The objective of this work was to evaluate the antibody titration against different protocols of anti-rabies primary vaccination in dogs. The study consisted of 32 dogs over 4 months of age divided into three experimental groups. The animals had their blood collected prior to the first vaccination, for the titration of anti-rabies antibodies. In Group 1, a blood sample and first anti-rabies vaccine were collected, followed by a new sample collection on days 30 and 180. In Group 2, a sample collection and first anti-rabies vaccine, a new sample collection and vaccine booster were performed anti-rabies on day 30, and only sample collection on days 60 and 180. In Group 3, sample collection and first anti-rabies vaccine were performed, sample collection and vaccine booster on day 7, sample collection and vaccine booster on day 30, and only sample collection on days 60 and 180. 120 serum samples were collected and sent to the Pasteur Institute in São Paulo where they were processed using the Fluorescent Focus Inhibition Reaction Test (RIFFT), in order to quantitatively determine the titre of anti-rabies antibodies. Descriptive statistics were performed and the results were analyzed using the Kruskal Wallis, Wilcoxon-Mann-Whitney test, which shows that protocol 2 concentrates and maintains the highest amount of antibodies in dogs first vaccinated on day 180... Miniature and small dogs obtained the highest amount of antibodies than medium-sized dogs. These data demonstrate that there is variation in the obtaining of anti-rabies antibodies in the face of the first vaccination in the population of dogs studied. Keyword: immunization, rabies, vaccines, canines, zoonosis